Gonadal restructuring during sex transformation in the protogynous greasy grouper Epinephelus tauvina (Forsskal) (Perciformes: Serranidae) - Mathew, Grace (Indian Journal of Fisheries, 2011)
This paper elucidates the developmental changes in the structure of the gonad during sex reversal in the greasy grouperEpinephelus tauvina (Forsskal). Sex transformation was induced artificially by administering the male hormone17 Î±-methyl testosterone to mature female fishes by adding the hormone to the feeding regime. The hormone treated fishesbecame mature males after the administration of a mean accumulated dose of 50-55 mg kg-1 body weight of fish, after9-12 weeks. Sex inversion was induced in both smaller and the larger fish, with no clear relationship with fish size and age.The study was carried out using histological techniques.